Academic criminology: A need for change - Moyer, Imogene L. (American journal of criminal justice, 1985)
An exploratory examination of criminology curricula, scholarly books, professional journals and reports is presented to substantiate the neglect of women in the works of most mainstream criminologists. Recent publications by Leonard (1982) and Schur (1984) suggest that this male view of criminology has distorted our definitions of crime and our responses to victims of male crime. These authors also indicate that the failure to include women in intellectual pursuits of the discipline has resulted in inadequate theories that do not explain women’s behavior and research based on false assumptions about the roles of men and women. While there have been numerous efforts to remedy this neglect of women during the last two decades (e.g., Bowker, 1977, 1980; Cullen, 1983; Reid, 1981, 1982), academic criminology continues to present a predominantly male perspective. In order to hasten the integration of women into the criminological curricula, theories, and research projects, this paper suggests changes in program policies that could be implemented by the leadership in professional associations (American Society of Criminology and Academy of Criminal Justice Sciences) that would encourage research in the area of women and crime as well as enhance the prestige and credibility of scholarship in this area of criminology.